Ultrasound Assisted Synthesis of Size-Controlled Aqueous Colloids for the Fabrication of Nanoporous Zirconia Membrane - Yan, Qiang; Qiu, Minghui; Chen, Xianfu; Fan, Yiqun (Frontiers in Chemistry, 2019)
Permeation and separation efficiency of ceramic membranes are strongly dependent on their nanoporous structures, especially on the pore size. In this work, ultrasound is employed to form the size-controlled ZrO2 nanoparticles, and prepared ceramic membrane with tunable pore size. Under the ultrasound treatment, H+ from water plays a key role in the synthesis process. The cavitation caused by ultrasound promotes the hydrolysis of precursor in water, which produces a large number of H+. These H+ will react with precipitant added and generate cyclic tetrameric units. Excess H+ can peptize cyclic tetrameric units and form an electrical double layer, resulting in a stable sol. Unlike ultrasound treatment, precipitant will react directly with the precursor and generate precipitation if there is no ultrasound added. Moreover, cavitation is good for the dispersion of cyclic tetrameric units. The particle size of Zr-based colloidal sol can be tuned in the ranges of 1.5 to 120 nm by altering molar ratio of precursor to precipitant, ultrasonic power density and radiation time. Meanwhile, ultrasonic power density and radiation time have effects on grain size and crystalline transition temperature of particles which influence performance of ceramic membrane. As a result, membranes exhibit high performance together with high permeability and desirable rejection. To develop such simple and controllable method for tuning particle size is extremely meaningful in the preparation of nanoporous ceramic membranes.